A study of an emerging trend in business reporting - The PowerPoint Report. - Cho, Yung Yung. (2008)
The trends in business reporting are seemingly changing in the current business environment, and new modes of reporting are seen to be surfacing to address this issue. More specifically, the PowerPoint report is one of the emerging trends in business reporting that many companies are seen to be adopting. As such, our report aims to analyse and evaluate the efficiency and effectiveness of the PowerPoint report, and its relevance to the current business reporting needs.